A systematic literature review of online teaching and learning strategies in language learning - Zuraina, Ali; Intan Syahidah, Zulkafa (Penerbit Universiti Sains Malaysia, 2025)
While the world is gradually recovering from the aftermath of the COVID-19 pandemic, teachers and learners are still coping with the impact of online teaching and learning (OTL). Within the brief period of a year (2020–2021), numerous studies were conducted across the globe in examining distinct factors and effects of OTL. This chapter aims to provide an overview of pertinent issues discussed in the previous literature particularly with regards to OTL strategies. Hence, a systematic review was conducted to synthesize key empirical findings from selected studies.